Pengujian Fungsional Website Sistem Informasi Persediaan Barang Toko “Jaya Makmur” Menggunakan Standar ISO/IEC 29119 - Dyah Masdyah; Lia Lianti; Chairul Anwar (CV. Multi Kreasi Media, 2025)
A web-based inventory information system plays an important role in supporting accurate and integrated stock management at Toko Jaya Makmur. This system is used to manage incoming goods, outgoing goods, transaction history, and real-time stock monitoring. To ensure that the system operates in accordance with operational requirements, a structured and well-documented software testing process is required. This study aims to conduct functional testing on the inventory information system website owned by Toko Jaya Makmur using the ISO/IEC 29119 standard as a testing reference. The testing method applied is black box testing, focusing on the dashboard module, incoming goods input, outgoing goods input, transaction history, and stock report features. Test case specifications were developed based on system usage scenarios. The test results indicate that all core system functionalities operate as expected, including data validation, automatic stock updates, and report export features in PDF and Excel formats. Based on the testing results, it can be concluded that the web-based inventory information system owned by Toko Jaya Makmur meets functional requirements and is suitable for supporting effective and efficient inventory management.